The Effect of Swelling on the Composition of a Mixed White Soil with Expansive Clays in the Godong - Purwodadi Area Km 49, Grobogan Regency - Bambang Pardoyo, Siti Hardiyati (International Journal of Advanced Science and Technology, 2020)
The effect of swelling and shrinkage on expansive clay soils can be influenced by weather factors, which are caused by heat and rain, besides that it is determined by the content of montmorillonite which often causes problems in civil buildings, especially on subgrade soils. Stabilization of expansive clay is needed to reduce swelling and shrinkage factors, by adding white soil material. The purpose of this study, the effect of swelling on the composition of the best white soil mixture in expansive clay. In this study as a stabilizer material using white soil from the Province of East Nusa Tenggara with a mixture of 1%, 2%, 3.5%, and 5% variations of the weight percentage with curing time of 7 days and 14 days, the test object was conditioned by OMC on the Standard Proctor. , by analyzing the characteristics of its physical and mechanical properties. The results of the research analysis of the properties index test, in general, on all percentages of the white soil mixture did not show significant changes and the engineering properties of the soil, for the white soil mixture with a percentage of 3.5% - 5%, with spacing time at 7 days and 14 days, the value Soil swell shows a positive trend.